Proceedings of the 14th International Conference on Interaction Design and Children 2015
DOI: 10.1145/2771839.2771917
|View full text |Cite
|
Sign up to set email alerts
|

A value sensitive design approach to parental software for young children

Abstract: Parental control software enables parents to support riskmanagement of their children's digital media use. However, tools to support online opportunities are left unexplored. This paper presents an explorative inquiry into stakeholder values related to parental software for young children, using a Value Sensitive Design approach. By studying values, we aim to illuminate design of parental software solutions that are responsive to the issues families find most important. We engaged in value exploration of corpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 14 publications
0
27
0
2
Order By: Relevance
“…Current research has emphasized the importance of balancing the needs of parents to monitor and manage usage with the needs of children to maintain the agency and autonomy that children need to develop into self-dependent adults [16,29,61]. Several studies have reported that appropriate balance in parental mediation can mitigate the negative aspects of digital media [37,24,58,6,33] and help to develop digital literacy and practical abilities in the use of digital devices [2]. It has been shown that mediation enforced by technology are more effective than mediation enforced by parents [19].…”
Section: Broader Implication Of This Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Current research has emphasized the importance of balancing the needs of parents to monitor and manage usage with the needs of children to maintain the agency and autonomy that children need to develop into self-dependent adults [16,29,61]. Several studies have reported that appropriate balance in parental mediation can mitigate the negative aspects of digital media [37,24,58,6,33] and help to develop digital literacy and practical abilities in the use of digital devices [2]. It has been shown that mediation enforced by technology are more effective than mediation enforced by parents [19].…”
Section: Broader Implication Of This Workmentioning
confidence: 99%
“…Research has been published, exploring both positive and negative consequences of this increase [58]. Important research being done includes topics such as children online safety [16,58], parental control [61,37], benefits of early education using mobile technology, inclusion of children in system and user interface (UI) design [59,57]. Systems and applications have also been built based on these research efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Nouwen et al [19] also point to values for children in their work with a value sensitive design approach towards parental software for young children. They state that the software developed must emphasize values related to how parents bring up their children using digital media aiming at control for safety, involvement, morality, independence and fun [19, p. 365].…”
Section: Why Consider Assumptions and Values?mentioning
confidence: 99%
“…Previous research within teen mobile safety has used this tripartite approach for identifying key technical design challenges with teens and parents (Czeskis et al, 2010); through this lens, research found that safety, trust, and privacy were values that caused tension between parents and teens. Nouwen, Van Mechelen, and Zaman (2015) found that parents value involvement, in addition to safety and control. VSD is well-suited for the context of adolescent online safety because it allows designers (in this case, college students) to reflect on core values that can help design better safety measures for teens.…”
Section: Literature Reviewmentioning
confidence: 99%